Review on bubble formation, rise and break-up in a gas-liquid system - Kulkarni, Amol A.; Joshi, Jyeshtharaj B. (Industrial & Engineering Chemistry Research, 2005)
The formation of gas bubbles and their subsequent rise due to buoyancy are very important fundamental phenomena that contribute significantly to the hydrodynamics in gas−liquid reactors. The rise of a bubble in dispersion can be associated with possible coalescence and dispersion followed by its disengagement from the system. The phenomenon of bubble formation decides the primitive bubble size in the system (which latter attains an equilibrium size), whereas the rise velocity decides the characteristic contact time between the phases which governs the interfacial transport phenomena as well as mixing. In view of their importance, we herein present a comprehensive review of bubble formation and bubble rise velocity in gas−liquid systems. The emphasis of this review is to illustrate the present status of the subjects under consideration and to highlight the possible future directions for further understanding of the subject. The bubble formation at a single submerged orifice and on multipoint sieve trays in Newtonian as well as non-Newtonian stagnant and flowing liquids is discussed in detail, which includes its mechanism as well as the effect of several system and operating parameters on the bubble size. The comparison of results has shown that the formulation of Gaddis and Vogelpohl22 is the most suitable for the estimation of bubble size in stagnant liquids. The special cases, such as bubble formation in reduced gravity conditions and weeping and in flowing liquids, are discussed in detail. The section on the rise of a gas bubble in liquid covers the various parameters governing bubble rise and their effect on the rise velocity. A comprehensive comparison of the various formulations is made by validating the predictions with experimental data for Newtonian as well as non-Newtonian liquids, published over last several decades. The results highlight that for the estimation of rise velocity in (i) pure Newtonian liquids, (ii) contaminated Newtonian liquids, and (iii) non-Newtonian liquids, the formulation based on the wave theory by Mendelson,190 Nguyen's formulation,155 and the formulation by Rodrigues,153 (last two, based on the dimensional analysis), respectively are the most suitable. The motion of bubbles in non-Newtonian liquids and the reason behind the discontinuity in the velocity are also discussed in detail. The bubble rise is also analyzed in terms of the drag coefficient for different system parameters and bubble sizes.

Hydrodynamics of bubble column reactors at high gas velocity: experiments and computational fluid dynamics (CFD) Simulations - Rampure, Mohan R.; Kulkarni, Amol A.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2007)
This paper focuses on the modeling of flow and mixing in a bubble column reactor operated at high gas velocities (up to 0.40 m/s). A dual-tip conductivity probe was used to measure local void properties such as local time-averaged gas holdup, chord length distribution, bubble velocity distribution, and interfacial area. Chord length distribution was converted to bubble size distribution, using the backward transformation method. Liquid-phase mixing time measurements were conducted using a conductivity probe. A computational fluid dynamics (CFD) model was developed to simulate the unsteady gas-liquid flow in a bubble column using commercial code FLUENT 6.2. The time-averaged flow properties predicted by CFD simulations were compared with the experimental data. The role of unsteady flow structures in mixing was studied. The `' multiple snapshots `' approach was used to simulate the mixing time using CFD. The mixing times that were predicted for all superficial gas velocities compared favorably to the measured values. This study of the hydrodynamic behavior of a bubble column at higher gas velocity provides a basis for understanding and simulating solid suspension (or solid mixing) in slurry bubble column reactors.

Mass transfer in bubble column reactors: effect of bubble size distribution - Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2007)
Mass transfer in a bubble column is analyzed in a different perspective. The experiments were performed in a bubble column reactor that was operated in a regime where the overall rate of absorption of gas into liquid was dependent on both the mass-transfer coefficient and the rate of reaction. Homogeneous catalytic oxidation of sodium sulfite was considered as a model reaction. The local instantaneous velocity data was measured using LDA in the presence of reaction and was used to yield the bubble size distribution at several locations in the column. The role of individual bubble size during mass transfer with chemical reaction was observed to vary. The findings suggest that a narrow bubble size distribution would help to achieve uniformity in the performance at bubble scale, so that an identical regime of mass transfer with reaction exists at the individual bubble level.

Continuous flow nitration of salicylic acid - Kulkarni, Amol A.; Nivangune, Nayana T.; Kalyani, Vishwanath S.; Joshi, Ramesh A.; Joshi, Rohini R. (Organic Process Research & Development, 2008)
Continuous flow nitration of salicylic acid using HNO3/AcOH was studied in the SS316 tubular microreactor. At specific reaction conditions, complete conversion of the reactant was achieved in less than 7 min. It yielded only mononitro derivatives with a higher selectivity of 5-nitrosalicylic acid. Presence of the lower amount of acetic acid in the reaction mixture was seen to be detrimental, leading to precipitation of the desired product (5-nitrosalicylic acid). Reaction at higher temperatures yielded byproducts. The continuous mode operation using the system comprising the microdevices was demonstrated for 2 h with consistent composition at the outlet.

Experimental analysis of the lift force on bubbles in a swarm - Kulkarni, Amol A. (Chemical Engineering Science, 2008)
The lift force acting on bubbles in a swarm has been estimated by analyzing the instantaneous velocity-time data obtained using LDA in a cylindrical bubble column. Phase distinction was achieved through the multiresolution analysis of the velocity-time data. Several important issues related to the transverse motion of bubbles subjected to a shear field have been discussed quantitatively. The actually measured bubble sizes, the respective slip velocity values in transverse and axial directions and the local shear rates (gamma) enabled the verification of known formulations for the lift coefficient (C-L) for bubbles. At many locations in the column the radial flux of the gas phase by turbulent dispersion and the radial slip were estimated. The radially inward movement of bubbles from low to high axial velocity (from column wall to center, i.e., C-L < 0) was observed at most of the measurement locations. The local lift coefficient was estimated using the transverse drag force and the values support the results from the material balance approach. The estimated C-L values showed a wide variation over the column cross-section. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Bubble; Bubble column; bubble size; hydrodynamics; LDA; lift force

Flow pattern in vortex diode: experiments and CFD simulations - Kulkarni, Amol A.; Ranade, V. V.; Rajeev, R.; Koganti, S. B. (AICHE Journal, 2008)
Vortex diodes are used as leaky nonreturn valves in applications, where it is desirable to avoid valves with moving parts. Despite their use in practice for several decades, no detailed analysis of the flow inside the vortex diodes is available. A strategy was derived for the CFD simulations of the vortical flow in diodes. A good agreement was seen between pressure drop (Delta P) across the inlet-outlet ports from CFD simulations, and the experimental data for five diode sizes. The simulations showed that in the reverse flow situation tangential velocity was dominant and resulted in conservation of angular momentum in the chamber until it reaches the axial exit port. This vortical motion induced a significant pressure drop (Delta P-r). The axial velocity gradient over the chamber cross-section helps in inducing relaminarization of the flow. In the forward flow mode, the fluid gets distributed radially over the chamber and exits through the tangential port, yielding low Delta P-f. The analysis showed that the performance of a diode is strongly affected by diode geometry, size, aspect ratio, nozzle configuration and Reynolds number. Among different configurations, the nozzles with entry port size equal to diode yielded higher diodicity. Simulations showed that using angle of divergence for diffuser sections of nozzles of the order of 7 degrees exhibited higher diodicity than smaller angles. It was also observed that at higher flow rates significantly higher diodicity was obtained using axial nozzles with larger radius of curvature for expander section. The modeling methodology and results presented will be useful for evolving better designs of vortex diodes.
Keywords: CFD; Diodicity; pressure drop; relaminarization; Vortex diode

Continuous flow nitration of benzaldehyde - Kulkarni, Amol A.; Kalyani, Vishwanath S.; Joshi, Ramesh A.; Joshi, Rohini R. (Organic Process Research & Development, 2009)
The nitration of benzaldebyde can be carried out in a safe manner in continuous mode using a microreactor system. Choice of a micromixer was seen to affect the performance of this two-phase reaction significantly The reaction time could he brought down to 2 min by increasing the reaction temperature and thereby taking advantage of higher heat transfer area. The simple T-micromixer is seen to be inefficient for two-phase reactions. Further scope of process intensification is also discussed.

Pressure drop across vortex diodes: experiments and design guidelines - Kulkarni, Amol A.; Ranade, Vivek V.; Rajeev, R.; Koganti, S. B. (Chemical Engineering Science, 2009)
Vortex diodes are used as leaky non-return valves in applications where it is desirable to avoid valves with moving parts. Despite their use in practice for several decades, no clear guidelines for design and optimization of vortex diodes are available. Detailed experimental study on flow and pressure drop characteristics of vortex diodes was therefore carried out to evolve such guidelines. The study covered a wide range of vortex diodes. The variation of diodicity (ratio of pressure drop for reverse and forward flow for the same flow rate) with respect to diode geometry, diode size (d(c)), aspect ratio (d(c)/h), nozzle configuration and Reynolds number (Re) was studied. The experimental results were critically analyzed to develop a design methodology. The methodology is shown to be useful for obtaining the diode dimensions that would yield the desired diodicity for the required operating flow rate. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Aspect ratio; Diodicity; Nozzles; pressure drop; Vortex diode

Fractal impeller for stirred tank reactors - Kulkarni, Amol A.; Jha, Neha; Singh, Abhishek; Bhatnagar, Sumit; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2011)
Stirred tank reactors are used for variety of applications at different scales of operation. The conventional impellers tend to develop regions having nonuniform energy dissipation rates in the stirred reactor. In this work, we propose a novel fractal impeller, which helps in reducing such nonuniformities and help develop a uniform randomness throughout the reactor. The impeller geometry is discussed in detail. Experimental measurements of the power consumption, mixing time, suspension quality, and the ability for gas dispersion were carried out, and the performance is compared with the conventional impellers. The impeller is seen to have a low power number, and it can generate a uniform suspension of particles even at relatively lower impeller speeds and can efficiently disperse gas into liquid to yield relatively higher gas hold-up values. The Fourier analysis of the power consumption time series data indicates that no specific prominent frequency events exist in the reactor, and the spectrum showed several frequency events to exist in the reactor with almost identical prominence.

Hydrodynamics of liquid-liquid dispersion in an advanced-flow reactor - Nieves-Remacha, Maria Jose; Kulkarni, Amol A.; Jensen, Klavs F. (Industrial & Engineering Chemistry Research, 2012)
Hydrodynamics and mass transfer of immiscible liquid-liquid flows are explored in an Advanced-Flow Reactor (AFR). These systems are emerging as one of the major commercial systems for small scale continuous flow chemistry, and characterization of the transport phenomena is critical for reaction implementation. With hexane/water as a model system, we use flow visualization techniques to determine drop size distribution, hexane holdup, and specific interfacial areas for a phase flow rate range of 10-80 mL/min. The complex geometry of the AFR with its continuously changing cross section along the flow path and strategically placed obstacles creates pressure changes that cause drop breakup and enhance mass transfer. Observations show that a wide range of average drop size (0.33-1.3 mm) can be achieved in the AFR depending upon the inlet flow rates and inlet composition. Pressure drop measurements are performed to estimate the power consumption and are used to compare the efficiency of AFR with conventional liquid-liquid contactors. The analysis shows that, similar to microreactors, the AFR can provide specific interfacial areas (1000-10 000 m(-1)) and overall mass transfer coefficients (1.9-41 s(-1)) a few orders of magnitude larger than conventional stirred tank reactors and also the static mixers.

Segmented flow synthesis of Ag nanoparticles in spiral microreactor: role of continuous and disperzsed phase - Kumar, D. V. Ravi; Bhagavatula L. V. Prasad; Kulkarni, Amol A. (Chemical Engineering Journal, 2012)
This work focuses on understanding the effect of segmented flow on the nanoparticle size distribution in a unidirectionally expanding spiral microreactor, where secondary flows are prevalent in the absence of segmentation. Stearic acid sophorolipid reduced/capped Ag NPs were synthesized in the aqueous phase and air or kerosene was used as inert phases for creating the gas-liquid and liquid-liquid segmented flow, respectively. While, in one case the reactant phase is in the form of dispersed phase slugs, in the other case it is in the form of continuous phase, each exhibiting a different behavior. The slug sizes and the slip velocity, both of which govern the nature of internal mixing in the reactant phase slug controlled the nanoparticle size distribution. This observation was consistent for both, gas-liquid and liquid-liquid segmented flows. The micromixer having smaller orifice diameter yielded smaller slugs and also a narrow particle size distribution. In general, the particle sizes were much smaller for gas-liquid flow rather than for liquid-liquid flow. Because of the unidirectionally expanding spiral geometry of the channel, at any given condition, unsteady behavior of slugs due to continuously varying radius of curvature results in variation in the slip velocity along the length of microchannel. This effect was seen to further narrow the particle size distribution than alone by the segmented flow. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Ag nanoparticles; Segmented flow synthesis; Sophorolipid; Spiral microreactor

Size-controlled flow synthesis of gold nanoparticles using a segmented flow microfluidic platform - Cabeza, Victor Sebastian; Kuhn, Simon; Kulkarni, Amol A.; Jensen, Klavs F. (Langmuir, 2012)
Segmented flow is often used in the synthesis of nanomaterials to achieve narrow particle size distribution. The narrowness of the distribution is commonly attributed to the reduced dispersion associated with segmented flows. On the basis of the analysis of flow fields and the resulting particle size distribution, we demonstrate that it is the slip velocity between the two fluids and internal mixing in the continuous-phase slugs that govern the nature of the particle size distribution. The reduction in the axial dispersion has less impact on particle growth and hence on the particle size distribution. Synthesis of gold nanoparticles from HAuCl4 with rapid reduction by NaBH4 serves as a model system. Rapid reduction yields gold nuclei, which grow by agglomeration, and it is controlled by the interaction of the nuclei with local flow. Thus, the difference in the physical properties of the two phases and the inlet flow rates ultimately control the particle growth. Hence, a careful choice of continuous and dispersed phases is necessary to control the nanoparticle size and size distribution.

Direct contact heat transfer via injecting volatile liquid in a hot liquid pool: generation and motion of bubbles - Kulkarni, Amol A.; Ranade, Vivek V. (Chemical Engineering Science, 2013)
Direct contact heat transfer via injection of volatile liquid is an effective strategy for removing heat from a viscous liquid pool. The rapid evaporation effectively removes heat and the generated bubbles move quickly to the top surface. In this paper, we present an experimental and phenomenological analysis of the evaporation of a drop in a slightly miscible liquid. The phenomenon was visualized using a two-dimensional transparent experimental set-up with a single inlet at the bottom. The videos were used to estimate bubble dimensions, its rise velocity, distance from the detachment point, and fraction of vapor and the liquid phases in the evaporating drop. The initial drop size, temperature difference between the hot fluid and the low boiling solvent and the nucleation rate governed the rate of change of the drobble (combined entity of drop and bubble) diameter and its rise velocity. A phenomenological model describing transient behavior of drobble (motion and heat transfer) is developed. The transient variation in the interfacial areas for heat transfer and the projected area were found to have effect on the predictions. The model and results will also provide useful basis for extending the work towards better understanding of direct contact heat transfer in viscous systems like polymerization reactors. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Bubble; Direct contact HT; Drobble; Drop; Evaporation; Slightly miscible liquids

Gas-liquid flow and mass transfer in an advanced-flow reactor - Nieves-Remacha, Maria Jose; Kulkarni, Amol A.; Jensen, Klavs F. (Industrial & Engineering Chemistry Research, 2013)
Hydrodynamics and mass transfer of gas-liquid flow are explored under ambient conditions in an Advanced-Flow Reactor (AFR), an emerging commercial system designed for continuous manufacture. Carbon dioxide/water is the model system used in this study for a range of flow rates for gas and liquid of 5.6-103 mL/min and 10-80 mL/min, respectively. Bubble size distribution, gas holdup, specific interfacial area, pressure drop, and mass transfer coefficients are determined from flow visualization experiments and compared with conventional gas-liquid contactors. These variables are mainly influenced by the inlet flow rates and inlet composition. Average bubble sizes ((d) over bar (B)) of 0.9-3.8 mm, gas holdup (epsilon(G)) of 0.04-0.68, specific interfacial areas ((a) under bar) of 160-1300 m(2)/m(3), and overall mass transfer coefficients (k(L)(a) under bar) of 0.2-3 s(-1) were obtained for the vertical orientation of the AFR. Although effect of gravity is present for this system, no significant effect on the hydrodynamic properties was observed. The measured pressure drop for vertical orientation (3.6-53.4 kPa) was used to estimate power consumption, which is used as a metric to compare mass transfer efficiency among different gas-liquid contactors. A power law relationship was obtained for the overall mass transfer coefficients in terms of power input and gas holdup, given by kL (a) under bar = 0.101P(w)(0.443)epsilon(0.459)(G). The design of the AFR with a series of heart-shaped confined sections with obstacles enhances continuous breakup and coalescence of bubbles providing interfacial areas and mass transfer coefficients 1 order of magnitude larger than other gas-liquid contactors, such as bubble columns (50-600 m(2)/m(3); 0.005-0.24 s(-1)) and spray columns (75-170 m(2)/m(3); 0.015-0.022 s(-1)), and 1 order of magnitude smaller than gas-liquid microchannels (3400-9000 m(2)/m(3); 0.3-21 s(-1)) or falling film reactors (20,000 m(2)/m(3)).

Synthesis of triangular gold nanoplates: role of bromide ion and temperature - Kumar, D. V. Ravi; Kulkarni, Amol A.; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2013)
Synthesis of noble metal triangular nanoplates is a kinetically controlled process in which temperature and packing defects play a major role. Nucleation and growth process of kinetically controlled reaction can be greatly influenced by temperature affecting the yield and edge length of the triangles. Through a conventional batch mode process, here we study the effect of temperature on nucleation and growth of gold triangular nanoplates and obtain some insight of the temperature effects on the final yield and edge length of triangles. The role of Br- ions in the synthesis of triangular nanoplates is studied by varying the amount of CAB and by replacing the CTAB with HBr. The results show that, while CTAB controls the edge length and yield of triangles, its use is not mandatory to attain plate like morphology. Finally we show that, while the initial temperature of the reaction mixture governs the nucleation rate and the rate of temperature rise governs the growth rate of particles, they along with the concentration of Br- ions control the edge length and yield. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Au nanotriangles; Halide ion effect; heat transfer; Kinetically controlled; Nature of gold precursor complex; Nucleation and growth; Optical properties

3D flow reactors: flow, hydrodynamics, and performance - Sharma, Mrityunjay; Reddy, Venkateswara S.; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2014)
A device comprised of a sequence of converging or diverging units aligned either in an axisymmetric or nonaxisymmetric manner can be used as a continuous flow reactor. Here we report the analysis of flow and hydrodynamics (pressure drop, residence time distribution, and mass transfer) for an axisymmetric geometry of a 3D flow reactor for single phase and two-phase flows. CFD simulations of the single phase flow have been used for identification of the precise geometrical configuration. The sequence of converging units as a flow reactor has been found to always be better than the sequence of diverging units. The residence time distribution analysis also favored the choice of converging flow as a better option. The performance of the device was verified by successfully carrying out a highly exothermic two-phase aromatic nitration of benzaldehyde (Delta H-r approximate to -172 kg/mol) with fuming nitric acid.

Continuous flow nitration in miniaturized devices - Kulkarni, Amol A. (Beilstein Journal of Organic Chemistry, 2014)
This review highlights the state of the art in the field of continuous flow nitration with miniaturized devices. Although nitration has been one of the oldest and most important unit reactions, the advent of miniaturized devices has paved the way for new opportunities to reconsider the conventional approach for exothermic and selectivity sensitive nitration reactions. Four different approaches to flow nitration with microreactors are presented herein and discussed in view of their advantages, limitations and applicability of the information towards scale-up. Selected recent patents that disclose scale-up methodologies for continuous flow nitration are also briefly reviewed.
Keywords: continuous flow; flow chemistry; microreactors; nitration; nitric acid; Tubular reactor

Continuous-flow meerwein arylation - Bhaya, Vinay G.; Joshi, Ramesh A.; Kulkarni, Amol A. (Journal of Flow Chemistry, 2014)
The continuous-flow Meerwein arylation is demonstrated for a set of few aryl donors (anilines and m-aminoacetophenone) and specific radical acceptors. Homogeneous catalyst (CuBr in HBr and CuCl in HCl) was used to facilitate the reaction. The effect of parameters, viz., temperature, catalyst concentration, residence time, and concentration of the radical acceptor on the yield of the arylated product, was studied. The yield of the aryl derivative obtained by continuous-flow syntheses was always better than the respective experiments in batch mode. Flow synthesis allows easy variation in these parameters and thus allows going close to the maximum possible yields in a system where the relative rates of different reactions create a complex situation. Temperature plays a crucial role by affecting the rates as well as by governing the system homogeneity. The nitrogen bubbles generated in the reaction helped to avoid any channel blockage.
Keywords: diazonium salt; flow chemistry; homogeneous catalyst; Meerwein arylation; micromixer; multistep synthesis

Discontinuous two step flow synthesis of m-aminoacetophenone - Tibhe, Jagdish; Sharma, Yachita; Joshi, Ramesh A.; Joshi, Rohini R.; Kulkarni, Amol A. (Green Processing and Synthesis, 2014)
The continuous flow nitration of acetophenone followed by reduction of the meta isomer has been demonstrated using simple tubular reactors. Because of ease of separation of the desired isomer from the first step, both steps are made continuous, but separately. The continuous flow nitration was carried out in a safe manner in a shorter reaction time than the conventional approach. The choice of micromixer was seen to affect the performance of the nitration reaction. The effect of different parameters on the yield of the desired product was studied. The reduction step with sodium sulfide was found to be economical and could be carried out efficiently at 70 degrees C using sodium sulfide in ethanol, using a silicone tube. Both steps were demonstrated for several hours, yielding a sufficiently large quantity (similar to 100 g) of m-aminoacetophenone at lab scale in a single day using simple tubular reactors.
Keywords: acetophenone; continuous flow synthesis; microreactor; nitration; reduction

Evaluation of multipoint dosing strategy in a miniaturized tubular reactor: nitration of salicylic acid - Debnath, Soujoy; Kienle, Achim; Kulkarni, Amol A. (Chemical Engineering & Technology, 2014)
A 2D non-isothermal reaction engineering model for a tubular reactor was developed for a complex reaction network of salicylic acid nitration. The influence of different operating and design parameters was studied to minimize the amount of secondary nitration products and limit the maximum temperature inside the reactor. Critical temperature effects were observed for larger reaction tubes, whereas close to isothermal conditions were perceived in smaller tubes. With single-point dosing of both reactants, complete conversion can be achieved but formation of secondary nitration products cannot be avoided. For a given number of dosing points, a suitable combination of the operating parameters allowed to achieve complete conversion and better yield of the desired product.
Keywords: Multipoint injection; nitration; Plug-flow reactor; Salicylic acid; Tubular reactor

pH-Dependent single-step rapid synthesis of cuo and cu2o nanoparticles from the same precursor - Nikam, Arun V.; Arulkashmir, Arulraj; Krishnamoorthy, Kothandam; Kulkarni, Amol A.; Bhagavatula L. V. Prasad (Crystal Growth & Design, 2014)
A single-step protocol to prepare Cu2O and CuO nanocrystalline particles from the same precursor by microwave irradiation has been developed using the pH of the solution as the only variable parameter. The utility of different bivalent Cu-precursors for synthesis of CuO and Cu2O nanoparticles was also investigated. The morphology, phase purity, and optical properties of these nanoparticles were analyzed using TEM, SEM, XRD, and optical spectroscopy. The band edges were determined using cyclic voltammetry. Field effect transistors based on CuO nanoparticles showed a hole mobility of 3.5 x 10(-2) cm(2) V-1 s(-1), making them a suitable candidate for energy-related applications. The effect of hydrazine vapor exposure on the IV-characteristics of CuO nanoparticles was also investigated. This revealed a decrease in source current with respect to time.

Two-phase flow in metal monoliths: hydrodynamics and liquid-liquid extraction - Deshpande, Jaydeep B.; Gosavi, Abha; Kulkarni, Amol A. (Canadian Journal of Chemical Engineering, 2014)
This work aims to explore the application of metal monoliths as a scale-up option for efficient liquid-liquid extraction. The pressure drop, mass transfer and residence time distribution are measured for low Ca (approximate to 10(-5)) with monoliths having three different cell densities. The cross-over section between two monoliths was seen to enhance mixing in the column. However, the RTD of two-phase liquid-liquid up-flow was inferior to the single phase RTD. For higher cell density substrates, the cross-over zones seem to cause trapping of slugs due to non-superimposing channel ends. Relatively high shear rates through the film of continuous phase helped enhance the mass transfer rates, thereby helping to achieve the desired extraction in a short column. The entrance sections and cross-over zones between the monoliths adversely affected the extraction for higher cell density monoliths. The analysis of data supports use of low cell density monolith for better performance and scale up.
Keywords: capillary; hydrodynamics; liquid-liquid extraction; monolith; slug flow

CRE for magic(modular, agile, intensified & continuous) processes - Ranade, Vivek V.; Sharma, Mrityunjay K.; Kulkarni, Amol A. (Chemical Engineering Journal, 2015)
Fine and specialty chemical industry caters to several key applications required for maintaining and enhancing quality of life. Most of these fine and specialty chemicals are still manufactured in stirred tank reactors operated in batch or semi-batch modes. A paradigm shift is necessary to transform these into new age, efficient and continuous processes and plants. In this paper, recent attempts of our group on developing MAGIC (modular, agile, intensified and continuous) devices, processes and plants for fine and specialty chemicals industry are discussed. The focus is on key chemical reaction engineering aspects of developing MAGIC processes. An attempt is made to evolve guidelines for designing MAGIC devices and reactors. The discussion will be useful to researchers as well as to industry practitioners. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Agile; Continuous; CRE; Intensified; Modular

Effect of interfacial mass transfer on the dispersion in segmented flow in straight capillaries - Deshpande, Jaydeep B.; Kulkarni, Amol A. (AICHE Journal, 2015)
The effect of interfacial mass transfer on the extent of dispersion in liquid-liquid segmented flow in straight capillaries is studied. In the absence of interfacial mass transfer, dispersion coefficient was seen to go through a minimum with increasing flow rates. In the presence of mass transfer, physicochemical properties of both the phases and slug lengths were seen to vary along the capillary length. The extent of dispersion was always higher in the presence of interfacial mass transfer. The predictions using axial dispersion model deviated noticeably for larger capillaries as the model does not account for varying buoyancy, dynamic contacting, and Marangoni convection. Simulations of a first-order interfacial reaction considering varying slug lengths showed a significant change in optimum operating parameters than the conventional approach. A special case of drop-on-demand type of controlled two-phase flow in capillaries was also studied. (c) 2015 American Institute of Chemical Engineers.
Keywords: capillary; dispersion; interfacial mass transfer; segmented flow; slugs

Continuous flow doebner–miller reaction and isolation using continuous stirred tank reactors - Yadav, Maruti B.; Kulkarni, Sourabh; Joshi, Ramesh A.; Kulkarni, Amol A. (Organic Process Research & Development, 2016)
Continuous flow Doebner–Miller synthesis of different quinaldines from respective anilines is demonstrated using sulfuric acid as a homogeneous catalyst. The extent of reaction was monitored for various parameters, namely, temperature, residence time, mole ratio of sulfuric acid to substrate, mole ratio of crotonaldehyde to substrate, and so forth. Continuous stirred reactors in series were used as a preferred configuration for this rection that generates byproduct in the form of sticky solid material. The approach has been extended for six different anilines, and the results are compared with batch reactions. Continuous stirred reactors in series with distributed dosing of crotonaldehyde facilitated a continuous flow reaction with lower byproduct formation, increased yields, and continuous workup and is a scalable approach.

Effect of number of branches on the performance of fractal impeller in a stirred tank: mixing and hydrodynamics - Mule, Gunwant M.; Lohia, Rajat; Kulkarni, Amol A. (Chemical Engineering Research & Design, 2016)
Number of blades of an impeller, impeller design and its positioning in a stirred tank is known to affect the mixing in a stirred tank reactor. The extent of non-uniformity in mixing from conventional impellers can be reduced significantly using a space-filling impeller like a fractal impeller. In this work, we report the effect of number of branches (and hence the number of blades) of fractal impeller on power consumption, mixing and hydrodynamics. Velocity measurements were carried out using ultrasonic velocity profiler (UVP). Measurements showed that the performance of fractal impeller with different configuration is equivalent, however, better than standard impellers in terms of mixing achieved per unit power consumption. No significant difference was observed in radial and axial mean velocity profiles for three different configurations. However, the tangential velocity was found higher for four branches than two and three branches FL Two distinct circulation loops were observed in upper as well as lower half of the vessel in r-z plane. Strong tangential flow throughout the baffled vessel helps to achieve good mixing even at low rotational speeds. (C) 2016 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Fractal impeller; Number of branches; UVP; Tangential velocity; Mixing

Interfacial precipitation and clogging in straight capillaries - Pal, Sayan; Kulkarni, Amol A. (Chemical Engineering Science, 2016)
Clogging of straight capillaries during interfacial precipitation (of common salt from saturated salt solution and acetone) was studied for a range of conditions that result in different flow regimes. The particle formation and clogging was explored using the images obtained by tracking a moving slug in real time. The flow regimes varied along the capillary length due to continuous mass transfer of acetone to water resulting in elongation of continuous phase slugs. In the slug flow regime, the precipitated particles formed solid shells/hemi spherical caps at the rear of acetone slugs, which eventually get detached from the interface. In the wavy parallel flow regime, where the interface is not flat, salting out was almost instantaneous and it led to faster clogging of the channels. Smaller Ca, i.e. lower flow rates or the use of smaller capillary length or using continuous fluid of relatively higher viscosity or lower interfacial tension can help to avoid or delay clogging. Formation of cohesive shells at the rear of a slug delayed clogging in the capillaries by delaying settling of individual particles. Parallel flow regime with a flat interface delayed the clogging significantly due to poor mass transfer as well as higher superficial velocities. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Clogging time; Flow regime; Interfacial precipitation; Micro-capillary; Porous shells; slug flow

Mixing of medium viscosity liquids in a stirred tank with fractal impeller - Mule, Gunwant M.; Kulkarni, Amol A. (Theoretical Foundations of Chemical Engineering, 2016)
Mixing of viscous liquids in a stirred tank is a daunting task. The present paper explores the possibility of using a fractal impeller for mixing of viscous liquids in a stirred tank. The analysis includes power consumptions characteristics, mixing characteristics and the flow patterns in the stirred tank. Ultrasonic velocity profiler (UVP) was used to measure the local velocities in the stirred tank. Fractal impeller found to exhibit different power consumption characteristics than known for conventional impellers. For the range of viscosities 0.58-0.192 Pa s, mixing time found to be directly proportional to the power consumption per unit mass. The normalised mean radial velocity profiles were found to be independent of fluid viscosities studied in the present work.

Selectivity engineering of the diazotization reaction in a continuous flow reactor - Shukla, C. A.; Kulkarni, Amol A.; Ranade, Vivek V. (Reaction Chemistry & Engineering, 2016)
In situ generated diazonium salts are useful intermediates for the synthesis of fine chemicals and active pharmaceutical ingredients. This paper presents a methodology for selectivity engineering of the diazotization reaction in a continuous reactor. The yield of diazotization was found to depend on mixing, dispersion, reaction kinetics, operating temperature and residence time. Initially, experimental data and an isothermal axial dispersion model were used for estimating mixing time. A correlation for estimating mixing time for different flow reactors is proposed. The model predictions were compared with the experimental data. The validated axial dispersion model and Central Composite Design (CCD) were used to optimize diazotization in a straight tube reactor (1.78 mL). The model was then used for scaling-up of aniline diazotization from a straight tube reactor to a proprietary AmAR3 reactor (scale-up ratio of ∼20). The initial concentration, inlet temperature, average heat capacity of the reaction mixture, mixing, residence time (distribution) and available heat transfer area per unit volume of the reactor were found to be the key parameters for scaling-up of the diazotization reaction. The presented approach and results will be useful to practicing chemists and engineers for enhancing the selectivity of diazotization reactions in continuous reactors.

Automating multistep flow synthesis: approach and challenges in integrating chemistry, machines and logic - Shukla, Chinmay; Kulkarni, Amol A. (Beilstein Journal of Organic Chemistry, 2017)
The implementation of automation in the multistep flow synthesis is essential for transforming laboratory-scale chemistry into a reliable industrial process. In this review, we briefly introduce the role of automation based on its application in synthesis viz. auto sampling and inline monitoring, optimization and process control. Subsequently, we have critically reviewed a few multistep flow synthesis and suggested a possible control strategy to be implemented so that it helps to reliably transfer the laboratory-scale synthesis strategy to a pilot scale at its optimum conditions. Due to the vast literature in multistep synthesis, we have classified the literature and have identified the case studies based on few criteria viz. type of reaction, heating methods, processes involving in-line separation units, telescopic synthesis, processes involving in-line quenching and process with the smallest time scale of operation. This classification will cover the broader range in the multistep synthesis literature.

Continuous flow telescopic oxidation of alcohols via generation of chlorine and hypochlorite - Sharma, Y.; Moolya, S.; Joshi, Ramesh A.; Kulkarni, Amol A. (Reaction Chemistry & Engineering, 2017)
A 3-step continuous flow oxidation of alcohols is demonstrated with continuous generation of chlorine as the first step followed by its use for the flow synthesis of high strength sodium hypochlorite. The solution is subsequently used for oxidation of alcohols in the presence of a catalytic amount of the nitroxyl radical “TEMPO”, which inhibits oxidation at the aldehyde stage. Selective oxidations of eight different alcohols were demonstrated. To achieve identical yields, the aromatic alcohols containing electron withdrawing groups needed a longer residence time than aliphatic alcohols.

Insights in the diffusion controlled interfacial flow synthesis of Au nanostructures in a microfluidic system - Kulkarni, Amol A.; Cabeza, Victor Sebastian (Langmuir, 2017)
Continuous segmented flow interfacial synthesis of Au nanostructures is demonstrated in a microchannel reactor. This study brings new insights into the growth of nanostructures at continuous interfaces. The size as well as the shape of the nanostructures showed significant dependence on the reactant concentrations, reaction time, temperature, and surface tension, which actually controlled the interfacial mass transfer. The microchannel reactor assisted in achieving a high interfacial area, as well as uniformity in mass transfer effects. Hexagonal nanostructures were seen to be formed in synthesis times as short as 10 min. The wettability of the channel showed significant effect on the particle size as well as the actual shape. The hydrophobic channel yielded hexagonal structures of relatively smaller size than the hydrophilic microchannel, which yielded sharp hexagonal bipyramidal particles (diagonal distance of 30 nm). The evolution of particle size and shape for the case of hydrophilic microchannel is also shown as a function of the residence time. The interfacial synthesis approach based on a stable segmented flow promoted an excellent control on the reaction extent, reduction in axial dispersion as well as the particle size distribution.

Microwave assisted batch and continuous flow synthesis of palladium supported on magnetic nickel nanocrystals and their evaluation as reusable catalyst - Nikam, Arun V.; Kulkarni, Amol A.; Prasad, Bhagavatula L. V. (Crystal Growth & Design, 2017)
Palladium nanocrystals (NCs) supported on nickel NCs (Pd/Ni) were synthesized in a continuous flow manner by the microwave-assisted method in the presence and absence of oleylamine. Parameters optimized for batch experiments were considered while performing continuous flow synthesis. The Pd/Ni NCs synthesized in the presence of oleylamine displayed good catalytic activity for hydrogenation of aromatic nitro compounds, and those bearing alkene, and alkyne moieties. The ferromagnetic character of the supporting nickel NCs allowed the recovery of the catalyst and these recovered catalysts could be reused several times.

Perspective article: flow synthesis of functional materials - Sebastian, Victor; Khan, Saif A.; Kulkarni, Amol A. (Journal of Flow Chemistry, 2017)
Continuous-flow synthesis of specific functional materials is now seen as a reliable synthesis approach that gives consistent product properties. This perspective article aims to survey recent work in some of the relevant areas and to identify new domains where flow synthesis of functional materials can be better than the conventional synthesis methods. It also emphasizes the need for developing high-throughput integrated synthesis and screening systems for almost all functional materials so that laboratory-scale recipes can be transformed into reliable manufacturing processes. New areas relevant to functional materials which have remained unexplored in flow synthesis are also highlighted.

Pinched tube flow reactor: hydrodynamics and suitability for exothermic multiphase reactions - Sharma, Mrityunjay K.; Potdar, Shital B.; Kulkarni, Amol A. (AIChE Journal, 2017)
A novel tubular flow reactor where a straight tube is modified by pinching it periodically at a fixed pitch and at different angles is presented. Pinched tubes (straight tube as well as helical coils) with different pitch and angles between successive pinching are studied. This work reports a detailed hydrodynamic study involving single and two-phase flow. Mixing experiments showed that having an angle of 90° between successive pinchs achieves the shortest mixing length when compared to lower angles. Pressure recovery along with sequence of high and low shear zones and change of flow direction imposed better mixing. Residence time distribution studies showed that higher number of pinch sections decreases the extent of dispersion, yet it deviates from plug flow. The performance is evaluated by carrying a homogeneous and two-phase aromatic nitration and also liquid-liquid extraction. Pinched tube presents an economical option as a flow reactor for conducting exothermic reactions. © 2016 American Institute of Chemical Engineers AIChE J, 2016
Keywords: pinched tube flow reactor; pressure drop; residence time distribution; mass transfer; reactions

Assessing the possibilities of designing a unified multistep continuous flow synthesis platform - Sharma, Mrityunjay K.; Acharya, Roopashri B.; Shukla, Chinmay A.; Kulkarni, Amol A. (Beilstein Journal of Organic Chemistry, 2018)
The multistep flow synthesis of complex molecules has gained momentum over the last few years. A wide range of reaction types and conditions have been integrated seamlessly on a single platform including in-line separation as well as monitoring. Beyond merely getting considered as `flow version' of conventional `one-pot synthesis', multistep flow synthesis has become the next generation tool for creating libraries of new molecules. Here we give a more `engineering' look at the possibility of developing a `unified multistep flow synthesis platform'. A detailed analysis of various scenarios is presented considering 4 different classes of drugs already reported in the literature. The possible complexities that an automated and controlled platform needs to handle are also discussed in detail. Three different design approaches are proposed: (i) one molecule at a time, (ii) many molecules at a time and (iii) cybernetic approach. Each approach would lead to the effortless integration of different synthesis stages and also at different synthesis scales. While one may expect such a platform to operate like a `driverless car' or a `robo chemist' or a `transformer', in reality, such an envisaged system would be much more complex than these examples.
Keywords: automation; continuous flow synthesis; cybernetics; multistep flow synthesis; unified platforms

Multi-step continuous flow synthesis of the cystic fibrosis medicine ivacaftor - Vasudevan, N.; Sharma, Mrityunjay K.; Reddy, D. Srinivasa; Kulkarni, Amol A. (Reaction Chemistry & Engineering, 2018)
A continuous flow ozonolysis method combined with a multi-step flow sequence is developed for the synthesis of the drug ivacaftor for the first time. Safe ozonolysis, a continuous flow quadruple reaction to construct a quinolone scaffold, and inline extraction followed by continuous phase separation are the key features of the present work. The feasibility of using a continuous mixed flow reactor, commonly referred to as a continuous stirred tank reactor (CSTR), is also investigated for the relatively slow reaction step. The current integrated multi-step flow synthesis can produce 7.2 g of the drug ivacaftor per day on a laboratory scale, which is sufficient to treat 50 patients per day. The present route can also be used as a general route for the synthesis of other related drugs such as quinolone antibiotics.

Pressure equalization approach for flow uniformity in microreactor with parallel channels - Madane, Ketan; Kulkarni, Amol A. (Chemical Engineering Science, 2018)
Numbering-up using parallel channels helps to achieve higher processing capacity while retaining the advantages of microreactors. However it may also lead to non-uniformity in flow across all the channels. Here we report the CFD simulations and experimental observations on the extent of uniformity in the flow from an assembly of several parallel channels. In the conventional parallel channel geometry, smaller channel size (<300 m) as well as higher fluid viscosity is seen to give better flow uniformity. Inequality in pressure distribution at the inlet of a large number of parallel channels is overcome by having two `pressure equalization slots' at an equal distance from inlet and outlets that open in the respective manifolds. Having such an arrangement helped to reduce the standard deviation in the flow by almost 90% when compared to the conventional geometry. However the modification was seen to increase the extent of back mixing to some extent. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: CFD; Experiments; Flow distribution; microreactor; Numbering-up; Parallel channels

Reaction engineering for continuous production of silver nanoparticles - Deshpande, Javdeep B.; Kulkarni, Amol A. (Chemical Engineering & Technology, 2018)
A scalable process for the production of silver nanoparticles that allows for complete conversion of the limiting reactant is analyzed in detail. The kinetics of silver nanoparticle synthesis using citrate reduction are investigated and used for development of a reaction engineering model to facilitate the reactor design. The effect of temperature, pH, concentration and mixing (axial dispersion) on the rates of nucleation and growth are analyzed quantitatively. An approach that considers reaction kinetics coupled with quality of dispersion is developed for reactor design as well as selection of reactor configurations for the synthesis of specific particle sizes. The developed approach has been applied for continuous production of 10-L suspension silver nanoparticles with very narrow particle size distribution.
Keywords: kinetics; particle size distribution; rate constant; Reactor design; Silver nanoparticle production

Antisolvent based precipitation: batch, capillary flow reactor and impinging jet reactor - Pal, Sayan; Madane, Ketan; Kulkarni, Amol A. (Chemical Engineering Journal, 2019)
A method for continuous antisolvent precipitation of ammonium perchlorate (AP) using a confined impinging jet reactor (CIJR) is studied. The geometry of the CIJR was optimized to achieve excellent mixing with a significant reduction in the particle deposition on walls. Initially, the experimental conditions were optimized in a batch system and then in a continuous capillary reactor. Later those conditions extended for antisolvent precipitation of AP in an impinging jet reactor using water and n-butyl alcohol as a solvent and antisolvent, respectively for optimum performance. The performance was compared with the experiments in batch mode as well as and in a continuous capillary reactor. Over a range of inlet jet velocity that corresponded to 1792 < Re < 7193 for the saturated aqueous solution of AP and 1135 < Re < 4553 for the antisolvent butanol phase, 8.98-16.98 mu m Ammonium perchlorate particles were attained.
Keywords: Ammonium perchlorate; Antisolvent precipitation; CFD; continuous flow; Impinging jet reactor; microparticles

Continuous flow solvent free organic synthesis involving solids (reactants/products) using a screw reactor - Sharma, Brijesh M.; Atapalkar, Ranjit S.; Kulkarni, Amol A. (Green Chemistry, 2019)
Here we report for the first-time various organic transformations such as aldol condensation, oxidation, nucleophilic substitutions, protection, acylations and coupling reactions using a mechanochemical approach at a controlled temperature using a single synthesis platform. Almost minimal solvents or solvent-free conditions are used, making it a very efficient and clean synthesis of various products. A jacketed screw reactor when operated at different temperatures (0 degrees C to 160 degrees C) and over a range of rotation speeds for changing the residence time (15 s-300 s) helped to achieve maximum conversion. This approach is also extended to the synthesis using substrates having different substitutions, heterocycles and steric hindrance.

Hydrodynamics and selectivity engineering of a multipoint dosing flow reactor - Shukla, Chinmay A.; Pal, Sayan; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2019)
This paper reports the suitability of a multipoint injection continuous flow reactor for carrying out a sequential reaction, while taking into account the associated hydrodynamics of such systems. Pressure drop was measured for different fluid injection patterns, viz., equal fluid dosing, decreasing dosing, and increasing dosing flow rates from the first to the last inlet. Moreover, residence time distribution was also explored. The data were compared with a conventional single-point injection. The extent of dispersion was found to be higher in the decreasing dosing profile compared to equally distributed dosing. Taking into account of these features, the suitability of such a reactor system for competitive-consecutive homogeneous nitration reaction was evaluated. The analysis was done on the basis of the Damkohler number (Da) for mixing and reaction. The rate-controlling phenomena were used to simulate the performance of the reactor for a range of a number of inlets, the mole ratio of reactants, and relative values of Da. The observations indicate that the multipoint injection is not beneficial for mixing controlled reactions. However, for reactions in the transient regime (i.e., 0.001 < t(m)/t(R) < 1000), it gives higher selectivity of the desired product.

Chapter 9. continuous flow synthesis of nanomaterials - Kulkarni, Amol A.; Jundale, Rajashri B. (Flow Chemistry, 2020)
Continuous flow synthesis of nanoparticles is now a well-accepted and reliable synthesis approach that gives consistent product properties. This chapter aims to do a critical analysis of the recent work in some of the relevant areas and gives specific recommendations where flow synthesis of nanomaterials can be realized as a reliable manufacturing process. The chapter also highlights the typical engineering issues that one needs to consider while transforming a batch synthesis protocol into continuous mode and its scale-up.

Continuous Flow Synthesis of Nanomaterials - Kulkarni, Amol A.; Jundale, R. B. (Continuous Flow Synthesis of Nanomaterials, 2020)

Continuous interfacial centrifugal separation and recovery of silver nanoparticles - Deshpande, Jaydeep B.; Navale, Govinda R.; Dharne, Mahesh S.; Kulkarni, Amol A. (Chemical Engineering & Technology, 2020)
Continuous-flow separation and recovery of silver nanoparticles (AgNPs) using an annular centrifugal extractor (ACE) is demonstrated. Separation was achieved at the liquid-liquid interface based on the balance between centrifugal force and the solubility of the capping agent. A mathematical model is presented to understand the mechanism in greater detail. The separation of poly(vinylpyrrolidone) (PVP)-coated AgNPs in an ACE using a strong immiscible solvent was performed. The material accumulated at the interface was separated periodically without discontinuing the operation. The method is also suitable for separation of large particles or 1D/2D nanostructures even employing a single annular centrifugal extractor. Stable AgNPs were selected for a detailed antimicrobial activity study.
Keywords: Annular centrifugal extractor; Antimicrobial activity; Continuous-flow separation; Liquid-liquid interface; silver nanoparticles

Effect of physical properties of dispersed phase on the residence time distribution in straight capillaries - Raval, Joy; Suryawanshi, Nalinee B.; Kulkarni, Amol A. (Chemical Engineering Science, 2020)

Efficient processing of reactions involving diazonium salts: meerwein arylation in an impinging-jet reactor - Shukla, Chinmay A.; Atapalkar, Ranjit S.; Kulkarni, Amol A. (Organic Process Research & Development, 2020)
This work reports a novel approach for performing high-throughput synthesis of Meerwein arylation in an impingingjet reactor. The multistep reaction was performed in a single reactor via in situ diazonium salt generation followed by Meerwein arylation. The work involves many iterations between experiments and simulations (where we integrate simulating the flow, heat transfer, and reaction simultaneously) for optimization of conditions in an inverted impinging-jet reactor. The effect of design variables viz. catalyst concentration, inlet temperature, and monomer mole ratio on the yield of the desired product was studied in detail, and the simulation results were used to plan the continuous experiments. An infrared camera was used to monitor the transient reactor temperature for steady-state analysis. The lab-scale inverted impinging-jet reactor with over 93% isolated yield can offer a space-time yield of 277.78 tons/m(3)/day. The numbering-up of an inverted impinging-jet reactor can be an effective way for cleaner production of products through typical Meerwein arylation.
Keywords: computational fluid dynamics; high throughput synthesis; impinging-jet reactor; IR camera; Meerwein arylation; Numbering-up

New TBAF complex, highly stable, facile and selective source for nucleophilic fluorination: applications in batch and flow chemistry - Said, Madhukar S.; Khonde, Nilesh S.; Thorat, Meghana N.; Atapalkar, Ranjit S.; Kulkarni, Amol A.; Gajbhiye, Jayant; Dastager, Syed G. (Asian Journal of Organic Chemistry, 2020)
Natural polysaccharides supported tetrabutylammonium fluoride (TBAF) complexes are prepared and found to be highly stable and selective fluoride source for well-renowned nucleophilic (SN2 type) fluorination reactions for the first time. Bacterial cellulose, plant cellulose, pectin, and starch derived TBAF complexes are synthesized, characterized (using SEM, TEM, and NMR techniques) and studied for their stability and reactivity. Heterogeneous bacterial cellulose-TBAF complex (NBu4(Bac-cell-OH)F) 1 was found to be highly stable and non-hygroscopic among all complexes, which gave high yields of fluorinated products in multi-gram scale in shorter reaction time. The primarily developed batch protocol was extended to solid-solid continuous flow reaction using an in-house built screw reactor, which furnished products in a few seconds of residence time (tR=20-25 sec) and excellent yields.
Keywords: Flow synthesis; fluorination; green chemistry; Sustainable Chemistry

Novel flow reactor for handling suspensions: hydrodynamics and performance evaluation - Sharma, Mrityunjay K.; Suru, Aditya; Joshi, Anuj; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2020)
A novel reactor concept that can handle solid particles without any moving components in the reactor is proposed and demonstrated in this work. The proposed reactor is designed by arranging the unique shape cavities in a sequence where inlet and outlets are positioned off-center to each other at specific angles and distance. Detailed flow simulation suggested that cavities with diameter D, having aspect ratio H/D similar to 1.53, outlet (having a diameter of 0.2D) positioned at 0.3D from the center and at 180 degrees with reference to the inlet is suitable for the expected performance. The proposed geometry of the reactor with the optimal geometrical configuration was fabricated and hydrodynamics (viz. pressure drop, mass transfer, and heat transfer, and residence time distribution) were studied. The reactor also offered high mass transfer coefficients and is useful for liquid-liquid reactions and extraction. A variety of solid suspensions (glass particles, activated carbon, starch particles, magnesium hydroxide) were tested over a wide range of flow rates for checking the solid handling capability of the reactor. The neutralization reaction of NaOH (with dissolved a-naphthol) with concentrated HCl that results in almost instantaneous precipitation of a-naphthol from the solution is used as a test reaction for a range of a-naphthol concentrations to change the suspension loading. It is shown that the proposed reactor can handle up to 22% (w/v) solid concentration without any clogging for a longer duration of the operation. However, for sticky solid particles, the same reactor would get clogged at the outlet ports for smaller diameters.

Selectivity engineering of Meerwein arylation in a continuous flow reactor: a modelling approach - Shukla, Chinmay A.; Atapalkar, Ranjit S.; Kulkarni, Amol A. (Reaction Chemistry & Engineering, 2020)
This paper presents a methodology for selectivity engineering of Meerwein arylation in a flow reactor. The reaction was optimized in batch mode and reaction kinetics were obtained over a range of temperatures and catalyst concentrations. A lumped kinetic model was formulated and the parameters were estimated using nonlinear regression. Furthermore, telescopic flow synthesis for Meerwein arylation via in situ diazonium salt generation and coupling was demonstrated. A non-isothermal model was developed and experimentally validated. The effect of initial concentration and inlet temperature on the yield of the desired product was estimated for various catalyst concentrations. The results from the simulations in terms of nondimensional numbers were used to find suitable operating conditions for Meerwein arylation.

Antisolvent based ultrasound-assisted batch and continuous flow precipitation of metformin hydrochloride particles - Pal, Sayan; Nikam, Arun V.; Kulkarni, Amol A. (Journal of Flow Chemistry, 2021)
Small sized particles of the antidiabetic drug metformin hydrochloride (MET.HCl) were produced by antisolvent based precipitation using an ultrasound assisted inverted jet reactor (IJR). This novel approach was implemented as a small passive mixer in which intensified turbulent mixing of the solution and the antisolvent occurred under controlled conditions. The optimized conditions for antisolvent precipitation (ASP) were investigated by studying the effect of solute concentration, antisolvent to solvent ratio and antisolvent temperature in batch systems. The optimized batch precipitation conditions were successfully translated into continuous flow process for the ultrasound assisted inverted jet reactor. The ability of the proposed clogging free inverted jet reactor approach can provide a scaled up alternative pathway to micro and millifluidic devices for manufacturing of small sized API particles, such as, MET.HCl for the formulations and encapsulations on an industrial scale.
Keywords: Continuous antisolvent precipitation; Jet-reactor; Metformin; supersaturation; Ultrasound

Continuous citrate-capped gold nanoparticle synthesis in a two-phase flow reactor - Damilos, Spyridon; Alissandratos, Ioannis; Panariello, Luca; Radhakrishnan, Anand N. P.; Cao, Enhong; Wu, Gaowei; Besenhard, Maximilian O.; Kulkarni, Amol A.; Makatsoris, Charalampos; Gavriilidis, Asterios (Journal of Flow Chemistry, 2021)
A continuous manufacturing platform was developed for the synthesis of aqueous colloidal 10-20 nm gold nanoparticles (Au NPs) in a flow reactor using chloroauric acid, sodium citrate and citric acid at 95 degrees C and 2.3 bar(a) pressure. The use of a twophase flow system - using heptane as the continuous phase - prevented fouling on the reactor walls, while improving the residence time distribution. Continuous syntheses for up to 2 h demonstrated its potential application for continuous manufacturing, while live quality control was established using online UV-Vis photospectrometry that monitored the particle size and process yield. The synthesis was stable and reproducible over time for gold precursor concentration above 0.23 mM (after mixing), resulting in average particle size between 12 and 15 nm. A hydrophobic membrane separator provided successful separation of the aqueous and organic phases and collection of colloidal Au NPs in flow. Process yield increased at higher inlet flow rates (from 70% to almost 100 %), due to lower residence time of the colloidal solution in the separator resulting in less fouling in the PTFE membrane. This study addresses the challenges for the translation of the synthesis from batch to flow and provides tools for the development of a continuous manufacturing platform for gold nanoparticles.
Keywords: Continuous manufacturing; Nanomaterials; Online analysis; phase separation; segmented flow

Design and scale-up of continuous di-nitration reaction using pinched tube flow reactor - Hussain, Arshad; Sharma, Mrityunjay; Patil, Suneha; Acharya, Roopashree B.; Kute, Mahesh; Waghchaure, Aishwarya; Kulkarni, Amol A. (Journal of Flow Chemistry, 2021)
Scale-up of the di-nitration reaction for synthesis of selective herbicide pendimethalin using only nitric acid in continuous flow is presented in this work. This work showcases an approach for smooth scale-up for an herbicide for a production capacity of 50 kg/day using a pinched tube reactor. The approach begins with the batch experiments followed by flow synthesis using a 1/8-inchSS316 helical coil tube where kinetics of the di-nitration was determined, and process optimization was done. Systematic approach was followed for quantification of heat transfer, mass transfer and residence time distribution and scale-up. Detailed scale-up methodology is presented with effect of relevant parameters for successful scale-up. Modular pilot plant with inline quenching, extraction and separation are some of the salient features presented in this work.
Keywords: continuous flow; nitration; Pinched tube; RTD; scale-up

Effect of object shape on the flow past microstructures in small channel - Mule, Gunwant M.; Kulkarni, Amol A. (Fluid Dynamics Research, 2021)
Flow past objects in microfluidics and microscale devices are used to perturb the flow and thereby achieve effective mixing and heat transfer. This paper presents the observations on the flow past bluff (elliptical, rectangular and triangular) cylindrical micropillars (objects) having different cross-sectional area in a micro-channel through 2D simulations. The pertinent range of Re based on object dimension (0.1 Re 150) was chosen to understand the wake dynamics that would remain relevant for comparison with literature data. Drag coefficient, recirculation region, critical Reynolds number for flow oscillations and vortex strength in a channel were studied. The drag coefficient was found to increase with aspect ratio of the object. The critical Re for flow oscillations was found to increase with the cross-sectional area of the object. The vortex strength in a channel was seen highest for triangular cylinder compared to elliptical and rectangular cylinder.
Keywords: 2D simulations; flow past objects; micro and mini-channels; micropillars; wake dynamics

Effect of wettability on hydrodynamics and mass transfer in small capillaries - Sampat, Chaitanya; Pal, Sayan; Kulkarni, Amol A. (Chemical Engineering Research & Design, 2021)
The wettability of the reactor wall has a significant effect on the interfacial liquid?liquid mass transfer rates in segmented flow. This work quantitatively demonstrates the importance of choosing the right material of construction of flow reactors to achieve the desired mass transfer performance. Glass and PTFE capillaries of identical diameter were used to study the effect of hydrophilic and hydrophobic surfaces on the hydrodynamics and mass transfer of the system. It was observed that for the overall mass transfer coefficient (kLa) changed by two orders of magnitude depending on the wettability of the continuous phase. The observations indicated that it is essential to achieve complete wetting of the capillary walls by the continuous phase for significant mass transfer enhancement. The observations are discussed on the basis of film thickness and slip velocity at the wall as well as the slip velocity at liquid?liquid interface. Predictions of the mass transfer coefficient using a model based on the interfacial and fluid properties showed excellent match with the experiments thereby allowing us to explore the effects of wettability on the overall mass transfer coefficient in greater detail. ? 2021 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Liquid?liquid slug flow; Mass transfer; Slip velocity; Wettability

Estimation of reaction kinetics for aromatic and heterocycles nitration in mixed acids through computational chemistry approach - Jadhav, Pandurang M.; Pandey, Raj K.; Kulkarni, Amol A. (International Journal of Chemical Kinetics, 2021)
Nitration of aromatic compounds and heterocycles in mixed acid environment is one of the regularly performed large-scale reactions in the chemical industry. Although the reaction mechanism of nitration of aromatics in mixed acid is well established, the development of a methodology for the evaluation of kinetics of exothermic aromatic nitrations in a simplified and accurate way is necessary. Here we evaluate the applicability of a kinetic evaluation methodology based on Hammett's acidity function, acidity function, and empirical activity coefficient for the nitration reaction. The contributions from the functional groups on the aromatic ring and quantitative structure-activity relationships technique are considered for these evaluations. Natural bond orbital and magnetic index nucleus independent chemical shift analyses were carried out to obtain the substitution constants. The rate constant and activation energy values were evaluated at various temperatures and sulfuric acid strengths. The results were validated by comparing with the experimental data from the literature for several molecules. The effect of various functional groups (viz carbonyl, carboxyl, methyl, and amine) substituted on the benzene ring was also evaluated. For a few identified substrates, the data were used for estimation of residence time needed for complete conversion in continuous stirred tank reactor and in a plug flow reactor to quantify the effect of substitution constant and strength of sulfuric acid. The approach will help select a suitable reactor.
Keywords: Aromatic nitration; computational chemistry; Hammett analogy; mixed acids; Reaction kinetics; reactor selection

Impingement dynamics of jets in a confined impinging jet reactor - Pal, Sayan; Madane, Ketan; Mane, Mayur; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2021)
The interaction of two impinging liquid jets in a confined impinging jet reactor (CUR) is explored. Multiphase flow simulations were performed using the volume of fluids (VOF) approach to investigate the impingement dynamics of liquid impinging jets, and single-phase CFD simulations have been performed to understand the turbulence and the mixing performance in the system. At identical inlet velocities, the liquid sheet formed on the impingement axis was found to move toward the liquid jet inlet of the lesser density fluid until reaching equilibrium. The formation and transient movement of liquid sheets are characterized for different jet velocities. An improved reactor geometry is proposed that reduces the wall effect on sheet formation and wall deposition on discharge points of jets. Upon breaking away from the impinging film, the two liquid phases are found to be intertwined in the form of ligaments and droplets after fragmentation of the sheet, providing a higher interfacial confirmed by performing high-throughput continuous antisolvent precipitation.

Inkjet printing of silver nanowires on flexible surfaces and methodologies to improve the conductivity and stability of the printed patterns - Patil, Prathamesh; Patil, Suneha; Kate, Prachi; Kulkarni, Amol A. (Nanoscale Advances, 2021)
Silver nanowires (AgNWs) are known to be used for printing on rigid as well as flexible surfaces. Here we have developed a systematic approach for using AgNWs synthesized by the polyol method for printing on flexible surfaces using a simple inkjet printing method. Optimized ink formulation used in this work comprises a mixture of Ag NWs suspended in ethylene glycol directly taken after synthesis and isopropyl alcohol. Using such formulation saves time and loss of material while transferring to other solvents, which is the usual practice. The printed patterns demonstrate high conductivity and stability over many months, which can revolutionize the applications of functional nanomaterials in low-cost printed electronics. The importance of fragmentation of nanowires only to achieve specific aspect ratios, to facilitate easy jetting and to prevent clogging is demonstrated. Varied concentrations (10 mg mL(-1) to 50 mg mL(-1)) of Ag NWs are used in ink formulations in order to print highly conductive patterns (resistance < 50 Omega sq(-1)) in a minimal number of passes. The same composition was also seen to facilitate simple and time-efficient nano-welding at room temperature, which improves the conductivity and stability of the printed patterns.

Multi-step synthesis of miltefosine: integration of flow chemistry with continuous mechanochemistry - Patil, Niteen B.; Atapalkar, Ranjit S.; Chavan, Subhash P.; Kulkarni, Amol A. (Chemistry-A European Journal, 2021)
Herein we report for the first time, an advanced continuous flow synthesis of the blockbuster Leishmaniasis drug miltefosine from simple starting materials by a sequence involving four steps of chemical transformation including a continuous mechanochemical step. First three reaction steps were performed in simple tubular reactors in a telescopic mode, while in the last step the product precipitated from the 3(rd) step was used for a continuous mechanochemical synthesis of miltefosine. When compared to a typical batch protocol that takes 15 h, miltefosine was obtained in 58 % overall yield in flow synthesis mode at the laboratory scale in a total residence time 34 min at synthesis rate of 10 g/hr, which is sufficient to treat 4800 patients per day.
Keywords: continuous flow; continuous mechanochemistry; miltefosine; multistep synthesis; reactive intermediates

Quantitative understanding of nucleation and growth kinetics of silver nanowires - Patil, Suneha; Kate, Prachi R.; Deshpande, Jaydeep B.; Kulkarni, Amol A. (Chemical Engineering Journal, 2021)
We have demonstrated that using polyol synthesis, it is possible to prepare high aspect ratio silver nanowires by controlling the experiments for process related issues which are usually ignored, viz. the overhead space in the batch reactor. It is found that by controlling the presence/absence of NOx gases with refluxing of nitric acid in the batch reactor with an overhead space of 80% volume, near complete conversion (-99%) of high aspect ratio NWs (-1000) can be attained. We provide a detailed understanding of other factors assisting in rapid polyol synthesis like temperature, stirring rate, Chloride ion concentration, optimal PVP weight ratios and PVP/AgNO3 ratio that can lead to high aspect ratio NWs. Besides the process parameters and reagent concentration effects, kinetic studies based on our nucleation and R-C Model evaluate the overall reaction rate constants for silver nanowires and the JMAK approach is used to theoretically validate our experimental results of the reactor headspace having strongest effect on the aspect ratios. Our study highlights the importance of various complications in the polyol synthesis, through detailed kinetic modelling and affixes values of temperature, reactor headspace, stirring rate and residence time in order to achieve reproducible synthesis of nanowires with complete conversion along with a method to separate these nanowires.
Keywords: Conducting inks; growth; Nucleation; Reaction kinetics; Redox-crystallization; Silver Nanowires

Scalable, sustainable and catalyst-free continuous flow ozonolysis of fatty acids - Atapalkar, Ranjit S.; Athawale, Paresh R.; Reddy, D. Srinivasa; Kulkarni, Amol A. (Green Chemistry, 2021)
A simple and efficient catalyst-free protocol for continuous flow synthesis of azelaic acid is developed from the renewable feedstock oleic acid. An ozone and oxygen mixture was used as the reagent for oxidative cleavage of double bond without using any metal catalyst or terminal oxidant. The target product was scaled up to more than 100 g with 86% yield in a white powder form. Complete recycling and reuse of the solvent were established making it a green method. The approach is significantly energy efficient and also has a very small chemical footprint. The methodology has been successfully tested with four fatty acids making it a versatile platform that gives value addition from renewable resources.

Solvent extraction of copper enhanced by mixing cavities in micromixer - Sheik, Abdul Rauf; Kulkarni, Amol A.; Sanjay, Kali (Solvent Extraction Research and Development-Japan, 2021)
A Y micromixer with a macroscopic mixing cavity at the inlet junction was developed. The effects of the mixing cavity on the improvement of extraction of copper by LIX 841 were investigated. The investigated parameters and their ranges were: overall flow rate: 10 - 200 mL/min; microchannel size: 0.5 - 1 mm and mixing cavity diameter: 5 - 20 mm. Extraction efficiency, volumetric mass transfer coefficient, kinetics and pressure drop were investigated. The extraction efficiency and the volumetric mass transfer coefficient in the cavity micromixer were significantly higher than the Y micromixer. The volumetric mass transfer coefficient ranged between 1 - 93 s(-1), and the pressure drop between 50 - 500 kPa. The residence time required in the micromixers was two orders of magnitude lesser than that of an agitated batch reactor.

Towards sustainable continuous production of azo dyes: possibilities and techno-economic analysis - Shukla, Chinmay A.; Kute, Mahesh S.; Kulkarni, Amol A. (Green Chemistry, 2021)
A novel continuous process for synthesizing azo dyes using a bubble column reactor is reported. Continuous experiments were successfully performed for Sudan-I dye and Solvent Yellow 16 dye with a yield [and productivity] of 92.04 +/- 3.50% [1.68 +/- 0.13 kg day(-1)] and 96.60 +/- 2.18% [1.92 +/- 0.04 kg day(-1)], respectively. Experiments were performed at a higher slurry concentration similar to 5% (w/w) without any clogging. The results were extended for performing a detailed techno-economic analysis for 5 TPD Sudan-I azo dye production as a case study. The results indicate that the cost of the continuous process is almost 4.68 times lower than that of the corresponding batch process. Furthermore, the footprint for a continuous plant can be lowered by 2.4 to 4.5 times when compared to the batch process depending on different refilling strategies for feed storage tanks. A continuous process may require 39-42% less water than the industrial batch process.

Evaluating suitability of confined impinging jet reactor for exothermic reactions: hydrodynamics, residence time distribution, and heat transfer - Khan, Muzammilanwar S.; Mane, Mayur; Kulkarni, Amol A. (AICHE Journal, 2022)
Effect of confinement (wall proximity) of a confined impinging jet reactor (CIJR) on the flow field, residence time distribution and heat transfer are explored, through experiments and CFD simulations. Hydrodynamic characteristics are evaluated for different parameters namely confinement, impinging jet velocity, temperature gradient, and so on. For 2 mm confinement, highest values of dispersion number and overall heat transfer coefficient are observed due to interaction of turbulent eddies followed by the effect of reactor wall proximity. For the CIJR having confinements above 10 mm, jet velocity need to be greater than 3 m/s to achieve both, excellent mixing efficiency and high heat removal rate. Empirical correlations for Dispersion and Nusselt numbers as a function of Re-j and L/D are obtained, over a range of 500 <= Rej <= 3000\$\$ 500\textbackslashle {\textbackslashmathit{\textbackslashoperatornameRe}}_j\text backslashle 3000 \$\$ and 5 <= L/D <= 35\$\$ 5\textbackslashle L/D\textbackslashle 35 \$\$, which correspond to jet velocity of 0.5-3 m/s. The present study gives a basis for designing CIJR suitable for rapid, homogeneous, exothermic reactions.
Keywords: confinement; exothermic reactions; heat transfer; impinging jets; residence time distribution

Introduction to the themed collection on digitalization in reaction engineering - Galvanin, Federico; Hartman, Ryan L.; Kulkarni, Amol A.; Nieves-Remacha, Maria Jose (Reaction Chemistry & Engineering, 2022)

Batch and continuous flow mechanochemical synthesis of organic compounds including APIs - Atapalkar, Ranjit S.; Kulkarni, Amol A. (Reaction Chemistry and Engineering, 2023)
Mechanochemistry is becoming an enabling technology for the synthesis of organic and inorganic compounds as well as for the synthesis of polymers as it underlines sustainability in a significant manner. Continuous mechanochemical synthesis further adds value to the approach through consistency, smaller footprint, and better energy efficiency. This review gives an indepth view of the present status of this subject along with critical engineering aspects that one needs to measure and monitor as eventually synthesis needs to be transformed into a process. The examples covered herein include the synthesis of organic compounds, viz., APIs, agrochemical intermediates, catalysts, and polymers. In the end, we also discuss the safety aspects of mechanochemical synthesis and recommendations for exploring this field further. Mechanochemistry is becoming an enabling technology for the synthesis of organic and inorganic compounds as well as for the synthesis of polymers as it underlines sustainability in a significant manner.
Keywords: acids; Amides; Force; solvent

Direct amidation of acids in a screw reactor for the continuous flow synthesis of amides - Atapalkar, Ranjit S.; Kulkarni, Amol A. (Chemical Communications, 2023)
A simple and efficient solvent-free protocol for continuous flow synthesis of amides at room temperature is developed using easily available starting materials. N-(3-Dimethylaminopropyl)-N & PRIME;-ethylcarbodiimide hydrochloride (EDC.HCl) was used as the reagent for the formation of an amide bond without using any metal catalyst or additives. A jacketed screw reactor when operated over a residence time of 30 300 s helped achieve almost complete conversion. This approach is extended for the synthesis of 36 derivatives and 2 bioactive molecules using different substrates having different aliphatic mono and di-acids as well as aromatic acids, including aromatic hetero-acid compounds and phenyl hydrazine. The target amide was scaled up to 100 g with an average 90% yield.

Dynamics of drop formation in the presence of interfacial mass transfer - Khan, Muzammilanwar S.; Kulkarni, Amol A. (Langmuir, 2023)
The dynamics of drop formation have been investigated in the presence of interfacial mass transfer through controlled flow visualization experiments. The mixtures of n-hexane (solvent) and acetone (solute) were used as a dispersed phase, having different initial compositions varying over a broad range. Drops were formed at the submerged position in the continuous phase (water) at the same operating flow conditions. The unsteady force balance model is developed to analyze the implications of the simultaneously occurring interfacial transfer of the solute on the formation dynamics in real time, and predictions are validated with experimental results. Based on initial compositions, the analysis of the transient drop shape shows a sharp transition in the drop formation regime. At lower initial solute concentrations, i.e., phi(0) < 0.2, axisymmetric drop formation occurs and the interfacial solute transfer has negligible effects on the formation dynamics. Over an intermediate range of solute concentrations, i.e., 0.2 < phi(0) < 0.5, Marangoni instability is triggered along the evolving interface, and therefore, the interface deformations and contractions occur during the drop formation. At phi(0) = 0.5, the drop takes highly nonaxisymmetric shapes and remains away from equilibrium until its detachment from an orifice. For phi(0) > 0.5, the spontaneous ejection of plumes of the solute results in the rapid generation of multiple droplets of smaller size. This work shows that higher solute concentration gradients not only lead to faster solute transport but also induce strong interfacial instability simultaneously. Thus, the coupled effects of transient change in composition and fluid properties govern the drop size and its formation time in such systems under non-equilibrium.

Effect of microwave heating on the residence time distribution in a tubular reactor - Sonawane, Jayesh R.; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2023)
Microwave(MW) heating has been revolutionary in various applications,including chemical synthesis. A nonconventional heating approach reducesthe reaction time significantly. For a continuous flow tubular reactorunder microwaves, the temperature would change from the inlet to theoutlet depending on the dielectric constant of the reaction mass,which would further change the physical properties, viz., the densityand viscosity of the material. Such changes in the physical propertieswould lead to nonideal flows and would affect the conversion as wellas selectivity for reactions. In order to understand the extent ofsuch a nonideality, here for the first time we have done systematicstudies of the residence time distribution in a helical coil reactor.The axial dispersion model has been modified to take into accountthe temperature-dependent physical properties of the fluid. The empiricalcorrelation for the dispersion number is obtained over the range of450 & LE; P (W) & LE; 1200 and 60 & LE; T (& DEG;C) & LE; 150. This study will help model thereaction kinetics as well as reactor design under microwave specificallyfor heat sensitive reactions where variations in the overall residencetime would affect the yield and selectivity of the end product.

Hydrodynamics, residence time distribution, and mass transfer in spiral coils in series - Khan, Muzammilanwar S.; Deore, Hital S.; Kulkarni, Amol A. (Industrial and Engineering Chemistry Research, 2023)
Here, we report the analysis of flow field, residence time distribution (RTD), and mass transfer for the novel design of a spiral coil reactor (SCR) consisting of five spiral coils connected in series. Each coil comprises 8 turns with minimum and maximum radii of curvatures of 15 and 45 mm, respectively. The SCR is made up of an SS 316 tube (1/8 in. approximate to 3.175 mm O.D. and 1.8 mm I.D.), with a total length of 3.89 m. Experiments, as well as three-dimensional (3D) CFD simulations, are carried out to study the effects of the flow rate (61 <= Re-in <= 1839) on spatial variations in velocity and pressure distribution within the individual coils of the reactor. The flow regime is observed to undergo a transition from stable laminar flow for a lesser Dean number (De < 50) to dominant secondary flow vortices for De > 80. During the flow from the inner to the outer turns of the coil, the tangential velocity increases with a decreasing curvature ratio (delta), and the opposite occurs during the flow from the outer to the inner turns of the coil. Experimental RTD results show that the extent of axial dispersion decays exponentially with increasing Re and remains constant for Re > 500. For liquid-liquid two-phase flow, the spiral coils in series offer a mass transfer coefficient comparable to those of static mixers and agitated contactors but with significantly lesser power consumption per unit volume. This work gives new insights into the design of a spiral coil reactor suitable to carry out single-phase and multiphase reactions efficiently as possibly the most space-filling option of tubular reactors with excellent transport characteristics.
Keywords: Gas- Liquid; heat transfer coefficient; Liquid Taylor Flow

Insights into the synthesis and kinetics of silver-on-silica core-shell particles - Jundale, Rajashri B.; Bari, Atul H.; Kulkarni, Amol A. (Langmuir, 2023)
In this study, a heterogeneous nucleation and growthmodel hasbeen developed to explore the formation mechanism of silver-depositedsilica core-shell particles based on the reaction kinetics.To validate the core-shell model, the time-dependent experimentaldata were quantitatively examined and in situ reduction,nucleation, and growth rates were estimated by optimizing the concentrationprofiles of reactants and deposited silver particles. Using this model,we also attempted to predict the change in the surface area and diameterof core-shell particles. The concentration of the reducingagent, metal precursor, and reaction temperature were found to havea strong influence on the rate constants and morphology of core-shellparticles. Higher rates of nucleation and growth often produced thick,asymmetric patches that covered the entire surface, whereas lowerrates produced sparsely deposited silver particles with a sphericalshape. The result revealed that by simply tuning the process parametersand controlling the relative rates, the morphology of deposited silverparticles and the surface coverage can be controlled while retainingthe spherical shape of the core. The present study aims to offer comprehensivedata pertaining to the nucleation, growth, and coalescence processesof core-shell nanostructures which will aid in the developmentand understanding of the principles that govern the formation of nanoparticle-coatedmaterials.

Settling and spreading behaviour of particle clusters in quiescent liquids in confined vessels - Pal, Sayan; Kulkarni, Amol A. (Particuology, 2023)
Here we report experiments on particle cluster settling at high Reynolds number in quiescent liquid contained in a vessel. The particles were observed to spread at the vessel bottom surface in a nearcircular annular shape after settling irrespective of the shape of the vessel cross-section and particle shape, size, and types. Effect of different parameters such as mass, type and aspect ratio of the particles, height, and viscosity of liquid was investigated on spreading behaviour. Formation of the hemispherical bottom cap of the cluster that bounces upon hitting the vessel bottom surface was found to be responsible for the final circular annular shape of the settled structure. Particle leakage from the cluster was seen in the form of a tail. In the liquid having viscosity beyond 100 cP, cluster breakage was observed that resulted in hindered settling and asymmetric shapes of finally settled particles. The observations are useful to understand the overall area over which settling and spreading of such clusters can be observed. (c) 2023 Published by Elsevier B.V. on behalf of Chinese Society of Particuology and Institute of Process Engineering, Chinese Academy of Sciences.
Keywords: Particle cluster; Settling; spreading; Temporal evolution

Transient response to perturbations in flow synthesis of citrate capped gold nanoparticles - Bari, Atul H.; Shukla, Neerja; Gavriilidis, Asterios; Kulkarni, Amol A. (Biochemical Engineering Journal, 2023)
This work reports the transient behavior of continuous flow synthesis of gold nanoparticles (Au NPs) when subjected to perturbations in operating conditions using controlled experiments. The intricacies are captured through a detailed mathematical model. Reversed Turkevich protocol was used for synthesis of Au NPs. The synthesis was first studied in batch mode to investigate the reaction kinetics and reproducibility of the process. The optimal set of operating conditions viz., residence time, flow rate, temperature was then used for flow synthesis in a 2 m, 1/16 & DPRIME;Polytetrafluoroethylene (PTFE) reactor with micromixer. Reactor clogging was avoided by using segmented flow. Inline UV measurement was used for real time monitoring of the process. Transient experiments were performed by abruptly changing the operating conditions. A mathematical model was found to be accurate in predicting the transient behavior of the exit precursor concentration and the particle size for unsteady state synthesis. Even a small change in process variables for short duration was found to disturb the quality of Au NPs for a significantly longer duration. Of the three operating parameters, the effect of temperature variation was seen to have a prolonged effect where the system remained in unsteady state for long time.
Keywords: continuous flow synthesis; gold nanoparticles; Particle size; segmented flow; Unsteady behavior

Understanding the nucleation and growth kinetics of the microwave-assisted synthesis of silver nanowires - Sonawane, Jayesh R.; Patil, Suneha; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2023)
Here, we present a detailed study of understanding the nucleation and growth kinetics of silver nanowire synthesis under microwave irradiation. The approach includes studying the effect of various parameters (viz., microwave power, reaction temperature, reaction time, substrate concentration, etc.) on the rate of nucleation and growth, as well as on the yield and morphology of silver nanowires. It is found that microwave power is the most important factor in leading to almost complete conversion of the substrate along with high aspect ratio nanowires in a short reaction time. Based on the observations, here, we have proposed a three-step growth kinetics mechanism for the synthesis of silver nanowires under the influence of microwaves. The approach comprises the autocatalytic growth of stable multiple twin particles after the nucleation process and their unidirectional growth to form nanowires. The FW autocatalytic model and the JMAK Avrami model were used to validate the proposed mechanism of AgNW formation based on our experimental results. The model predictions match very well with the conversion and yield of AgNWs. At the optimized conditions, wires with a 42 nm diameter and 94% yield were achieved within 4 min.

Continuous flow ozonolysis of cardanol for greener synthesis of bio-based monomers - Kulkarni, Sphurti P.; Kulkarni, Amol A. (Journal of Flow Chemistry, 2024)
Synthesis of bio-based monomers via continuous flow ozonolysis of cardanol using a simple tubular reactor is demonstrated. The direct ozonolysis of cardanol produces unique monomer 8-(3-hydroxyphenyl) octanal (HPOA) and heptanal along with several other oxidation products. Maximum 47% yield of HPOA with 54.3% conversion of cardanol was obtained at 0 degrees C in 9 s. The complete conversion of cardanol was obtained at the ozone to cardanol molar flow ratios greater than 2 at all temperatures varied in the range of -10 degrees C to 20 degrees C. Owing to large gas-liquid ratios, the mass transfer limitation for transfer of ozone from gas to liquid was negligible; however, the extent of axial dispersion in the liquid phase was significant at lower liquid flow rates. The non-ideal behavior was incorporated in the axial dispersion model to predict the conversion of cardanol. Examination of kinetic rates by both ideal plug-flow model and plug-flow with axial dispersion model revealed that the reaction is fast and is least influenced by the axial-dispersion in the reactor at prevailing operating conditions. The findings of the current study show that continuous flow technique enables a simple and safer synthesis of high-value bio-based monomers via ozonolysis of cardanol compared to traditional batch methods.
Keywords: Axial-dispersion model; Cardanol; continuous flow; Helical coil; Ozonolysis

Continuous flow synthesis of mesoporous silica particles with tunable size and structure - Jundale, Rajashri B.; Prasad, Bhagavatula L. V.; Devi, R. Nandini; Kulkarni, Amol A. (Industrial and Engineering Chemistry Research, 2024)
We have developed a continuous process to prepare mesoporous silica particles of different sizes and narrow size distribution in a tubular reactor. The method is based on the use of well-known Stober synthesis in the presence of cationic surfactant in methanol-water solvent system and trimethylbenzene as pore swelling agent to form porous silica particles. We observed that reaction parameters had enormous effects on particle size, distribution, and numerous morphological aspects. We demonstrated that these properties may be modified by adjusting the reaction temperature, base concentration, and surfactant concentration. MSPs of spherical morphology with variable size from 400 to 1000 nm produced with the surface area >600 m(2)/g and pore diameter of 2-4 nm. Large scale production is demonstrated by increasing reactor volume using 1/4 in. PTFE tubing from 20 to 163 mL, with this production of MSPs increased from 0.35 to 3 g/h. The method has been extended for high yield production at the kilogram scale using this approach, which will pave the way toward the industrialization of mesoporous silica based materials.

Experimental and kinetic modelling studies for the design of fixed bed methanol reactor over CuZA catalyst - Bagwan, Farahanaz M.; Dongapure, Pavan; Kulkarni, Amol A.; Vasireddy, Satyam Naidu (Chemical Engineering Research Design, 2024)
Direct conversion of CO 2 via hydrogenation to value-added chemicals is a vital approach for utilising CO 2 emitted into the atmosphere. In this paper, a critical analysis of reaction kinetic modelling studies is explored in a fixed bed reactor to improve methanol yield for different H 2 to CO 2 ratios by simulating a lab-scale reactor for adiabatic and isothermal conditions. The feed inlet temperature and pressure variations are applied to study the effect of both configurations on methanol production. The results show that the isothermal configuration yields 2.76% more methanol yield compared to the adiabatic reactor. The effect of H 2 to CO 2 molar ratios of 3, 6 and 9 on the performance of the catalyst and the influence of CO and CO 2 hydrogenation is investigated with model simulations. The overall methanol yield is increased from 19.03% to 36.41% with increase in H 2 to CO 2 molar ratio from 3 to 9. Experiments are performed using commercial copper-based catalyst for different temperatures of 210, 230 and 250 degrees C at a pressure of 40 bar for H 2 /CO 2 of 3 and GHSV of 720 h -1 as well as at optimal temperature of 250 degrees C and 50 bar with varying H 2 /CO 2 of 3, 6, 9 for 3 g and 6 g catalyst. The maximum methanol yield of 2.53% and space time yield of 13.59 mg/g cat .h is obtained at H 2 /CO 2 ratio of 9.
Keywords: CO2 conversion; CuZA catalyst; H2 toCO2 molar ratio; Kinetic modelling; Methanol

Model predicted optimization of experimental set-up and process conditions for microwave-assisted synthesis of silver nanowires - Sonawane, Jayesh R.; Kulkarni, Amol A. (Chemical Engineering Journal, 2024)
This work presents simulations led optimization of choice of a reactor for an experimental set-up for the continuous production of silver nanowires with certain constraints in terms of yield, reaction time, and dimensions of nanowires. The choice of reactors based on the simulations of reaction kinetics for nucleation and growth phases of driving the optimization of an experimental set-up and subsequent optimization of process conditions to maximize the yield of nanowires of desired dimensions. The optimized reactor configuration is dictated by the reaction kinetics and using a microwave in continuous mode becomes unavoidable. This makes the approach highly reproducible as well as scalable. The integration of conventional and microwave heating is simulated and subsequently optimized experimentally to attain a significant increase in nanowire yield under steady-state conditions with less than 15 min of residence time. The precise control over the rate in different reactor configurations governing nucleation, accelerated growth followed by slow growth to complete the conversion of precursor enables higher selectivity of nanowires with controllable dimensions resulting in 100 gm production per day using simple set-up. We systematically examined key reaction parameters, including the concentration of metal ions, residence time, and different reactor configurations. Our approach successfully yielded AgNWs with 40-60 nm diameter and 15 mu m length. The cost associated with this process for synthesizing AgNWs is less than 10\$ per gram. This study highlights the potential of continuous, high-throughput processes for controlling nanowire size and yield through advanced reactor engineering.
Keywords: Continuous synthesis; Microwave; Reactor design; Silver Nanowires

Scaling-up continuous production of mesoporous silica particles at kg scale: design & operational strategies - Jundale, Rajashri B.; Sonawane, Jayesh R.; Palghadmal, Anil V.; Jaiswal, Hemant Kumar; Deore, Hital S.; Kulkarni, Amol A. (Reaction Chemistry & Engineering, 2024)
This paper demonstrates a continuous flow pilot-scale production of highly porous mesoporous silica particles (MSPs) via a soft template based technique. The study presents pilot scale reactor design, fabrication and production of mesoporous silica particles with a 1 kg per day production rate. The extent of mixing and overall performance of the system were evaluated by conducting a hydrodynamic study, including the estimation of the heat transfer coefficient and dispersion number. Nanoparticle synthesis in a clogging-free manner is the key challenge in moving towards large scale production and commercial applications. This article presents a comprehensive study on the effect of key parameters for successful scaling up of the process. We have also addressed challenges faced and how these are overcome by troubleshooting the process. Different strategies were used to prevent the clogging of the reactor, which involved reactant dilution, periodic pulsation and slug flow (two phase flow). Among them, slug flow allows us to operate the reactor continuously for several hours without clogging and wall-deposition problems. It helped produce morphologically well-defined and near-monodisperse particles. With this process, the production is validated at a scale of 85 times compared to that of a laboratory system (from 22 mL to >1.5 L), enabling a production rate of 20-50 g h(-1).

Understanding the effects of physical properties of composite drop on its formation dynamics in presence of interfacial mass transfer - Khan, Muzammilanwar S.; Kulkarni, Amol A. (Industrial and Engineering Chemistry Research, 2024)
Dynamics of drop formation is studied in presence of interfacial mass transfer through controlled flow visualization experiments and lumped force balance based model. Experiments were conducted using eight different combinations of ternary systems, involving variations in initial composition and physical properties of drop phase over a broad range. A new image analysis method is reported to accurately measure the size of deformed, nonaxisymmetric drops. Based on flow visualization and analysis of drop shape, four modes of drop formation are identified, including (i) mass transfer free mode, (ii) interfacial instability mode (Marangoni effects), (iii) dripping, and (iv) jetting, with progressively increasing solute concentrations. Exceptions to these modes are observed for tetrahydrofuran-toluene and tetrahydrofuran-benzene mixtures, in which the drop remains in mass transfer free mode even in presence of higher solute concentrations. Model predictions of real time change in drop volume show excellent match with experimental results for all of the systems under study. The analysis of force balance implies that the interplay between (i) surface tension force and (ii) the combination of buoyancy and force due to kinetic energy controls the drop detachment time as well as the final drop volume. Therefore, for identical operating conditions, transition in drop formation time occurs from 4 s to 65 ms, depending on the density difference and interfacial tension between contacting phases. The present findings provide detailed insights into the formation dynamics of composite drops, which are commonly encountered in liquid-liquid extraction and various multiphase operations.

Confined impinging jet reactor for high-throughput continuous flow mononitration of salicylic acid - Khan, Muzammilanwar S.; Shaikh, Tabrez R.; Kulkarni, Sphurti P.; Patil, Abhishek A.; Kulkarni, Amol A. (Organic Process Research & Development, 2025)
Novel approach is reported for highly efficient continuous mononitration of salicylic acid using confined impinging jet reactor (CIJR) with a vent. Initially, controlled semibatch reactions are optimized to achieve complete conversion and formation of mononitro products with very high selectivity for 5-nitrosalicylic acid (5-NSA). Further, the combination of computational fluid dynamics simulations and experiments is employed to optimize CIJR design and operating flow conditions, suitable to yield only mononitro products with excellent control over mixing, heat transfer, and liberation of fumes during continuous flow reaction. Detailed analysis of internal flow patterns, rate of heat generation, and concentration distribution inside the CIJR facilitated the optimization of present exothermic reaction in a safe manner. In less than a minute, complete salicylic acid (SA) conversion with good yield and better selectivity for 5-NSA is achieved using the CIJR. Safety and clogging issues are addressed effectively, even at a relatively lower mole ratio (1:5) of SA:acetic acid (AcOH). The present approach is quite scalable using the numbering-up strategy, with advantages viz. nonfouling, high throughput, and the small footprint of CIJR.
Keywords: computational fluid dynamics; confined impinging jet reactor; high-throughput synthesis; salicylic acid nitration

Continuous flow solvent-free and catalyst-free mechanochemical production of rhodamine B dyes and their derivatives - Purohit, Mukesh; Shaikh, Tabrez Rafique; Kulkarni, Amol A. (Chemical Communications, 2025)
In this communication, we have described a simple and efficient, catalyst free and solvent-free protocol for the continuous flow synthesis of rhodamine B dyes developed from 3-diethyl amino phenol and phthalic anhydride. Nearly 95% conversion was achieved within 12 min using a jacketed single screw reactor. This method is further used for the synthesis of six derivatives with 70-84% yield, which can be compared to 85% yield from a 1-hour long batch synthesis involving a catalyst.

Continuous flow synthesis of metal nanowires: protocols, engineering aspects of scale-up and applications - Sonawane, Jayesh R.; Jundale, Rajashri; Kulkarni, Amol A. (Materials Horizons, 2025)
This review comprehensively covers the translation from batch to continuous flow synthesis of metal nanowires (i.e., silver, copper, gold, and platinum nanowires) and their diverse applications across various sectors. Metal nanowires have attracted significant attention owing to their versatility and feasibility for large-scale synthesis. The efficacy of flow chemistry in nanomaterial synthesis has been extensively demonstrated over the past few decades. Continuous flow synthesis offers scalability, high throughput screening, and robust and reproducible synthesis procedures, making it a promising technology. Silver nanowires, widely used in flexible electronics, transparent conductive films, and sensors, have benefited from advancements in continuous flow synthesis aimed at achieving high aspect ratios and uniform diameters, though challenges in preventing agglomeration during large-scale production remain. Copper nanowires, considered as a cost-effective alternative to silver nanowires for conductive materials, have benefited from continuous flow synthesis methods that minimize oxidation and enhance stability, yet scaling up these processes requires precise control of reducing environments and copper ion concentration. A critical evaluation of various metal nanowire ink formulations is conducted, aiming to identify formulations that exhibit superior properties with lower metal solid content. This study delves into the intricacies of continuous flow synthesis methods for metal nanowires, emphasizing the exploration of engineering considerations essential for the design of continuous flow reactors. Furthermore, challenges associated with large-scale synthesis are addressed, highlighting the process-related issues. This review comprehensively covers the translation from batch to continuous flow synthesis of metal nanowires (i.e., silver, copper, gold, and platinum nanowires) and their diverse applications across various sectors.

Continuous flow telescopic synthesis of 3-methoxy propiophenone by the grignard reaction - Wankhede, Pranali; Kulkarni, Amol A. (Organic Process Research & Development, 2025)
The synthesis of 3-methoxypropiophenone 1, a crucial intermediate in the production of the analgesic tapentadol hydrochloride, was investigated using a multistep continuous flow process. The approach is based on the Grignard reaction. A series of continuously stirred tank reactors (CSTRs) were employed: the first reactors facilitated the continuous generation of Grignard reagents 3, which then reacted with propionitrile in the next CSTR to yield 1. This was followed by quenching, neutralization, and phase separation, conducted under varying temperatures and residence times. When compared to a 50% yield from an optimized batch synthesis protocol, a continuous flow synthesis helped achieve an 84% yield of the desired product in a much shorter reaction time. A kinetic model was developed to predict the Grignard reagent formation and product yield, revealing that the mass transfer effect is insignificant at a higher stirring rate. The approach is highly scalable for the synthesis of pharmaceutical intermediates.
Keywords: batch and continuous reaction; flow chemistry; Grignard reaction; heterogeneous kinetics

Residence time distribution of powders in a vertical single screw reactor: experiments using salt-coated tracer particles and simulations - Rajendra, R. Sriram; Palgadhmal, Anil V.; Kulkarni, Amol A. (Particuology, 2025)
The use of single and twin-screw extruders for solid-phase reactions is a promising method to intensify a process in a more sustainable manner. In this manuscript, we report a detailed analysis of the residence time distribution (RTD) in vertical single-screw reactors. The results will help in the selection of the right screw design that would help achieve the desired residence time, which is necessary for a reaction to happen. Experiments were conducted in three vertical screw reactors (having fixed shaft diameter) with varying dimensions using granular free-flowing powders of sodium chloride and silica with a mean particle size of similar to 25 mu m. RTD behavior was modeled using the radial particle velocities in the screw reactor's centrifugal field. Further, a method is proposed for estimating the axial dispersion coefficient of dry powders in such sheared flows using true and bulk densities of the powder and the screw shear rate. This dispersion coefficient is used in the axially dispersed plug flow model to describe the RTD behavior of screw reactors with acceptable accuracy. The theoretically predicted and experimentally obtained dispersion coefficients are found to be similar thereby confirming the suitability of the model. (c) 2025 Chinese Society of Particuology and Institute of Process Engineering, Chinese Academy of Sciences. Published by Elsevier B.V. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Bulk density; Centrifugal field in screw reactor; Particle inertial number; Powder dispersion coefficient; Powder flow; Single-screw extruder

Selection of tubular reactor configurations for a confined space: analysis of space-fillingness and performance - Mali, Chaitanya R.; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2026)
Introducing bends or coiling in a tubular reactor promotes Dean vortices, which enhance radial mixing as well as heat and mass transfer. Exploring compact geometries that strengthen curvature-induced mixing is highly beneficial for continuous flow synthesis across scales. Despite their advantages, selecting an appropriate configuration of tubular reactors in a given space (jacket) requires careful evaluation of multiple factors, including energy efficiency, dispersion behavior, heat transfer performance, and spatial compactness. This paper presents a holistic framework for selecting an optimal configuration of a tubular reactor within a confinement (jacket) based on energy efficiency, dispersion behavior, heat transfer, and spatial compactness. Ten distinct configurations are explored based on geometrical characterization and single-phase Computational Fluid Dynamics (CFD) simulations. Each configuration is evaluated for flow patterns, pressure drop, residence time distribution (RTD), and jacket-side flow distribution. The results demonstrate that geometric design, especially the number and arrangement of bends, has a pronounced impact on reactor performance, influencing both compactness and dispersion characteristics. A combined qualitative-quantitative assessment is employed, utilizing radar plots (which capture key simulation and geometric data) and a K-means clustering unsupervised learning algorithm, along with a derived performance index (Pi), to rank configurations based on their geometric attributes. This approach forms a robust basis for selection and design guidance. The study indicates that while individual designs offer specific advantages, coil geometries such as multihelix, spiral, and elongated spirals deliver optimal overall performance.